Sprinting, isokinetic strength, and range of motion of ankle joints in Turkish male and female national sprinters may have a relationship - (:unkn) unknown (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2012)
Aim: We aimed to observe the isokinetic muscular strength differences of the ankle-foot complex of sprinters of both sexes to understand the effectiveness of the ankle and subtalar ranges of motion on the sprint performances of elite athletes. Materials and methods: Elite Turkish national sprinters (n = 11; 5 females and 6 males) were assessed regarding their ankle joint isokinetic performance (30 degrees/s and 120 degrees/s), joint ranges, and sprint times. Results: A significant difference was observed between the average power of the right dorsiflexors (P < 0.001) of female athletes and the right invertors (P < 0.05) of male athletes at 120 degrees/s for the 100-m sprint time. The average powers of the right (P < 0.05) and left (P < 0.05) evertors of the male athletes at 30 degrees/s were significantly negatively correlated with sprint time. Additionally, only the plantar flexion range was significant for male athletes' sprint times, and the dominant invertors' peak torque at 120 degrees/s in female athletes was significant (P < 0.05). Conclusion: The strength of the nondominant side dorsiflexors of female athletes and the nondominant invertors of male athletes are important in decreasing the strength asymmetry to disregard the strength of the nondominant side in relation to sprint performance. Key words: Sprint performance.
Keywords: Sprint performance; sex; ankle muscles; peak torque; average power; MUSCLE STRENGTH; TENDON; PERFORMANCE; POWER; RELIABILITY; MOMENT; SPEED; LEG